The Global Minimum Tax and the taxation of MNE profit - Hugger, Felix (OECD Taxation Working Papers, 2024)
The paper assesses the impact of the global minimum tax (GMT) on the taxation of multinational enterprises (MNEs), based on a comprehensive dataset capturing the global activities of large MNEs. It has four key findings. First, the GMT substantially reduces the incentives to shift profits. Second, the GMT is estimated to very substantially reduce low-taxed profit worldwide through lower profit shifting and top-up taxation. Third, the GMT is estimated to increase CIT revenues. Finally, the GMT is estimated to reduce tax rate differentials across jurisdictions with potential impacts on the allocation of investment and MNE activity